EFFECTIVE MANAGEMENT OF HOUSING AND COMMUNAL SERVICES RESOURCES OF TERRITORIAL COMMUNITIES IN WAR CONDITIONS (Development Service Industry Management, 2025)
The article substantiates the importance of housing and communal services of territorial communities as a key element in ensuring the livelihoods of the population and the sustainable development of administrative and territorial units in wartime. The resource provision of housing and communal services was analyzed and the main factors affecting it were determined: financial and economic, organizational and management, technical and technological, social and external (war challenges, economic crisis). It is shown that the management of the resources of territorial communities should be based on a comprehensive approach, which involves a combination of state and non-state sources of financing, increasing the efficiency of the use of resources and applying strategic planning tools to achieve the socio-economic goals of the community. An algorithm for determining the priorities and directions of using the resources of territorial communities in wartime conditions has been developed, which involves diagnosing the state of the community, identifying directions (critical, without which life in the community is impossible, supportive and developing), allocating resources, including the budget, taking into account various scenarios. It is substantiated that in the conditions of war, the main task of local authorities is primarily to ensure stability, which consists in the maintenance of vital systems, social stability, rational use of limited resources, gradual restoration of community potential after the crisis. Peculiarities of strategic planning of resource management in crisis conditions are highlighted. Methods of effective management of community resources under unstable economic and security conditions are summarized.The study used a systematic approach, methods of analysis and synthesis, comparative and abstract-logical methods to generalize the factors of resource provision of housing and communal services of territorial communities. Structural-functional and graphic methods are used to develop an algorithm for determining priorities and directions of resource use in wartime conditions.The article will be useful to representatives of local self-government bodies, heads of communal enterprises, specialists in the field of public administration and regional development, who deal with issues of resource provision of territorial communities. The research materials can be used by scientists, education seekers and state institutions during the formation of the policy of restoration and development of housing and communal services in the conditions of war and post-war recovery.Keywords: resource provision, communal enterprises, housing stock, housing and communal services, territorial community.
Keywords: resource provision; communal enterprises; housing stock; housing and communal services; territorial community